The concept of «Urban Locality» in signature worldview of Timur Zulfikarov (Eurasian Journal of Philology Science and Education, 2016)
The article deals with the substantial components of the basic concept of «Urban Locality». National-cultural and individual layers are identified. It holds in-detail description of the «passive layer» of the concept of «Urban Locality». As the material of description the works of the famous contemporary writer Timur Zulfikarov were considered. The researcher highlights language means that represent the concept of «Urban Locality»: lexical units in the literal sense, metaphorical designations, comparisons, epithets, figurative associations, symbolic assimilation. The focusing on the context of language units representing the concept of «Urban Locality» gives an opportunity to reveal the periphery of the concept, to describe the meaning shades that are not fixed in any lexicographical sources, and finally to discover the peculiarities of studied concept in linguocultural aspect.
Keywords: concept; signature components of the concept; the concept of the active layer of the concept; the passive layer of the concept; language tools; a metaphor; epithet.